MBE growth and optimization of the InGaAs/InAlAs materials system for quantum cascade laser - Tian, Wang; Zhang, Dong-liang; Zheng, Xian-tong; Yang, Ruo-ke; Liu, Yuan; Lu, Li-dan; Zhu, Lian-qing (Frontiers in Materials, 2022)
High material quality is the foundation for the excellent performance of quantum cascade lasers. This paper investigates the growth conditions for InGaAs/InAlAs/InP superlattices combined solid-source molecular beam epitaxy with metal-organic chemical vapor deposition. Based on the optimization of growth conditions of InGaAs buffer epilayers, the effects of the growth temperature, interruption time, and V/III flux ratio on the quality of InGaAs/InAlAs/InP superlattices were systematically investigated. High-resolution x-ray diffraction and atomic force microscopy prove that this optimized InP-based superlattice has excellent periodicity and sharp interfaces.